THE GENUS DURIO Adans. (Bombac.) - A. J. G. H. KOSTERMANS (REINWARDTIA, 1958)
The genus Durio comprises, as far as known, 27 species. The centre of distribution is Borneo with 19 species, followed by Malaya with 11 species and Sumatra with 7 species. It is likely, when Sumatra will be better explored, that this island will prove to have many more species. An exclave of the area of distribution is found in Burma, where one endemic species occurs. The common Durio zibethinus Murr. probably originated in Borneo or in Sumatra. It is now widely cultivated outside of its former area and in many places it has become spontaneous. The genus Durio is subdivided into two subgenera: Durio and Boschia Kosterm. & Soegeng, according to the way of dehiscence of the anthers (with a longitudinal slit in the former, with an apical pore in the latter). A key to the species is proposed. A map is added, to show distribution and endemism. Each species is amply described and provided with a drawing . Economic and ecological data are given.